Kong : Skull Island [videorecording (DVD)] - Vogt-Roberts, Jordan; Hiddleston, Tom; Jackson, Samuel L.; Larson, Brie, 1989-; Jackman, Henry (Henry Pryce) (Warner Bros. Entertainment, 2017)
A scientific exploratory mission on an uncharted Pacific island becomes a battle for survival when a giant gorilla and other monsters become aware of their presence.